KOMPOSISI DAN KEANEKARAGAMAN TUMBUHAN PADA HABITAT KETAK (Lygodium circinatum (BURM.(SW.) DI PULAU LOMBOK, NUSA TENGGARA BARAT - Endah Wahyuningsih; Eny Faridah; Budiadi Budiadi; Atus Syahbudin (Lambung Mangkurat University-Indonesia, 2019)
This research was aimed to identify composition and biodiversity of species in the natural habitat of ketak. This research used purposive systematic sampling by survey technique based on altitude i.e. 0-249, 250-499 and 500-750 m asl. There are 10 of observation plot with dimension of 20 m x 20 m at each altitude and total plot was 30 plots. The results showed that the composition at the seedling level at each altitude was 15 species in 11 families; and 13 species in 11 families and 8 species in 6 families. Sapling level there was 13 species in dari 10 families; 7species in 7 families and 10 species in 8 families. Pole level, there was 11 species in 9 families; 9 species in 8 families and 12 species in 10 families,And at the tree level at each altitude there was 15 species in 10 families and 17 species in 14, and 9 species in 8 families. The value of the species diversity index Shannon (H ') at all structure level and in all altitude classifications was known that in medium categories,only at sapling and pole level in low category, and value of index (Ds) was known that all level in high catecories. The index of species richness Margalef (Dmg) in medium categories, only at the altitude of 500-750 m asl was in low category, and value of Simpson species richness index (Dmax) was known that all level in high catecories. The value index of species evenness (E) and index (Es) at all altitudes in the stable category.